Ammonium Dinitramide as a Prospective N–NO2 Synthon: Electrochemical Synthesis of Nitro-NNO-Azoxy Compounds from Nitrosoarenes - Alexander S. Budnikov; Nikita E. Leonov; Michael S. Klenov; Mikhail I. Shevchenko; Tatiana Y. Dvinyaninova; Igor B. Krylov; Aleksandr M. Churakov; Ivan V. Fedyanin; Vladimir A. Tartakovsky; Alexander O. Terent’ev (Molecules)
In this study, the electrochemical coupling of nitrosoarenes with ammonium dinitramide is discovered, leading to the facile construction of the nitro-NNO-azoxy group, which represents an important motif in the design of energetic materials. Compared to known approaches to nitro-NNO-azoxy compounds involving two chemical steps (formation of azoxy group containing a leaving group and its nitration) and demanding expensive, corrosive, and hygroscopic nitronium salts, the presented electrochemical method consists of a single step and is based solely on nitrosoarenes and ammonium dinitramide. The dinitramide salt plays the roles of both the electrolyte and reactant for the coupling. Despite the fact that many side reactions can be expected due to the redox-activity of both the reagents and target products, under optimized conditions the synthesis is performed in an undivided cell under constant current conditions with high current density and can be easily scaled up without a reduction in the product yield. Moreover, the synthesized nitro-NNO-azoxy compounds are discovered to be potent fungicides active against a broad range of phytopathogenic fungi.